REALIZATION OF GROUP TWO-OPERAND OPERATIONS STRONG STABLE CRYPTOGRAPHIC ENCODING - Пустовит, Михаил (SWorldJournal, 2020)
Particular attention deserve the operations that in the process of information transformation on the basis of the subdued sequence provide the achievement of strong cryptographic encoding, which means the maximum uncertainty of the cryptographic transfor